Proposta de molde manual e confecção de tijolos ecológicos vazados - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The application of ecological bricks in rural constructions emerges as an advantageous solution, not only for its positive impact on the environment, but also for its economic and social benefits, when using renewable raw materials, such as soil and agricultural residues, in its composition. This study's main objective was to enable the manufacture of ecological bricks using a manual mold, following the guidelines of the NBR 8491 standard (ABNT, 2012). The mold was developed using AutoCad® 3D software and made with cedar wood. Type B hollow ecological bricks with dimensions (24cm x 12cm x 7cm) were molded from the mixture proposed by Campagnolo (2022), with 80% wind soil, 10% Portland cement and 10% rice husk silica. During tests, the mold proved to be efficient, ensuring precise filling and adequate compaction of the mixture. Despite facing challenges in the demoulding stage, the use of a Kraft paper base resolved this issue, preserving the integrity of the bricks. After a curing period of 28 days, simple compressive strength and water absorption tests were carried out. The tests revealed a variation in individual values, ranging between 4.15 MPa and 7.56 MPa, with an average of approximately 5.80 MPa, exceeding the minimum limit established by NBR 8492 (ABNT, 2012), of 2.00 MPa. . Also, according to NBR 15270-1 (ABNT, 2023), ecological bricks presented an average compressive strength (fbm) of 5.80 MPa and an estimated characteristic resistance (fbk, est) of 5.20 MPa, exhibiting performance superior to normative standards of 4 Mpa. The average water absorption was 12.28%, well below the maximum water absorption limit established by the NBR 8491 standard, which is 20%. In summary, the manufacture of ecological bricks using manual molds and alternative raw materials emerges as a promising alternative for rural communities, not only offering a sustainable and efficient option for construction, but also promoting the use of local resources and strengthening community development.
Keywords: Engenharia agrícola; Tijolos ecológicos; Construções rurais; Agricultural engineering; Eco-friendly bricks; Rural constructions; CNPQ::CIENCIAS AGRARIAS